(3EdbGA Gdajd GdRgQjs 15 (3WQjbI dJbhd eG JYfjg hJYfj eG Jbhdgs - (3eGcaGQdGf, Hds ((3GdQjGVs (3ecJHI LQjQs, 2008)
"(3gPG GdcJGH jJfGhd LejY fhGMj GdJhGUd GdTNUj HCSdhH HSjW heSd(B" "(3MJi GPG cfJ JHJYO Yf cJH eSGYOI GdPGJ (B,(3aYdjc Gf JLQH gPG GdcJGH GdXQja h GdeejR LOkG(B" "(3fGOQG eG jchf GdTF eajOoG heeJYkG CjVkG hdcf gPG GdcJGH eeJY ddZGjI aj bQGAJg hedF HGdMceI hGdaGFOIs
5 12 20
Keywords: (3GdGJUGds; (3Yde GdfaS GdJWHjbjs